Improved Partnership Working for Local Authority Transport Planning - John Forrester (European Journal of Transport and Infrastructure Research, 2009)
Diverse perspectives need to be brought together to facilitate the organisational delivery of more sustainable transport plans and policies. This necessitates close-working partnerships and good cross-sector learning. This paper looks at the rationales for design of, and anticipated roles for, two tools to assist this process: one a guide to cross-sector and intra-organisational partnership working written specifically for local authority transport practitioners; and the other an online framework within which practitioners can better identify and utilise other products from the research programme. Whilst grounded in UK research and experience, the lessons learned are generic to the European context. The paper also investigates the success of DISTILLATE’s own interdisciplinary approach and relates this to the literature, in particularly to the idea of ‘double loop learning’ by which individuals and organisations (research and practitioner) can acquire the new knowledge necessary to make the step-change towards more sustainable transport systems and practices. This is followed by a discussion of the implications of this for supporting decision-making more widely in the field of transport and infrastructure.